Cryptic diversity of Eviota (Teleostei: Gobiidae) and their habitat use in the shallow waters of Okinawa Island - Hanahara, Nozomi (Marine biodiversity, 2023)
Eviota , known as dwarf gobies, is a diverse genus of marine fishes comprising more than 120 species found throughout the Indo-Pacific Ocean. Previous studies have suggested that morphologically similar cryptic species of Eviota may exist and that the species diversity may be significantly underestimated. This study evaluated the diversity of Eviota species in three habitat types (tidal flats, reef flats, and moats) in the shallow waters (0–1 m in depth at low tide) of Okinawa Island using morphological characteristics and molecular phylogenetic analysis. Eleven morphospecies were classified into 17 molecular operational units (MOTUs), and cryptic species for which speciation may have occurred relatively recently were detected in the morphospecies Eviota abax , Eviota japonica , Eviota queenslandica , and Eviota prasina . Most MOTUs exhibited only one habitat use, whereas three MOTUs were found in multiple habitats. Among each cryptic Eviota species, both habitat segregation and habitat overlaps were found. Therefore, habitat segregation among cryptic Eviota species may occur at spatial scales such as in this study, or at finer spatial scales, and multiple factors should be considered regarding speciation in Eviota .